2020
DOI: 10.4274/jpr.galenos.2019.51422
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Pediatric Nurses’ Oral Care Practices

Abstract: Oral care is a standard practice used to reduce ventilator-associated pneumonia in intensive care units and in the treatment of chemotherapy-induced oral mucositis. This research examines the oral care practices of pediatric nurses. Materials and Methods: This is a descriptive and cross-sectional study. Its sample was composed of 90 nurses working in the pediatric services of a university hospital in western Turkey from March to December 2016. The research data was collected using a sociodemographic data form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition to assessing the effect of integration of oral care practices into the training of nursing professionals, 12 studies reported on the general oral care practices of nursing professionals [4,44,46,55,57,61,[65][66][67][68][69][70]. In general, there was variability observed in nursing practices related to oral healthcare.…”
Section: Oral Care and Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to assessing the effect of integration of oral care practices into the training of nursing professionals, 12 studies reported on the general oral care practices of nursing professionals [4,44,46,55,57,61,[65][66][67][68][69][70]. In general, there was variability observed in nursing practices related to oral healthcare.…”
Section: Oral Care and Practicesmentioning
confidence: 99%
“…In general, there was variability observed in nursing practices related to oral healthcare. Five studies reported that nurses often used oral care solutions (saline, chlorhexidine, hydrogen peroxide solution, sodium bicarbonate solution, and distilled water/tap water) for mouthwash [4,44,57,65,70]. Various studies reported the use of foam swabs/swabbing (61-91.9%) [44,61], moisturizers (53-98.9%) [44,55], cotton/gauze swabs (69.9-93,5%) [55,61], saline (20-82.7%) [61,70], chlorhexidine (12.2-97.8%) [54,57,61,70], hydrogen peroxide solution (31.8%) [61], sodium bicarbonate solution (20.8-75.6%) [61,70], distilled water/tap water (4.3-17.9%) [55,61,70], mouthwash (57.8-88.2%) [55,70], toothbrushes (17.8-70%) [44,70], suction toothbrushes (93.5%) [55], and manual toothbrushes (49.5%) [55] for oral care.…”
Section: Oral Care and Practicesmentioning
confidence: 99%